2010
DOI: 10.1253/circj.cj-09-0849
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein-Cholesterol/High-Density Lipoprotein-Cholesterol Ratio Predicts Lipid-Rich Coronary Plaque in Patients With Coronary Artery Disease - Integrated-Backscatter Intravascular Ultrasound Study -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp igh serum levels of low-density lipoprotein-cholesterol (LDL-C) are a major risk factor for atherosclerotic cardiovascular disease. 1 Controlled lowering of LDL-C levels is important for primary and secondary prevention of coronary artery disease (CAD). 2,3 A previous study showed a significant reduction in coronary plaque volume at blood LDL-C levels <100 mg/dl after statin therapy. 4,5 The Framingham study demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
(20 reference statements)
0
30
0
1
Order By: Relevance
“…3 This finding indicates that LDL/HDL-cholesterol ratio might be a more important risk factor than LDL-cholesterol itself in CAD patients, and should be investigated further. …”
Section: Article P 1392mentioning
confidence: 88%
See 1 more Smart Citation
“…3 This finding indicates that LDL/HDL-cholesterol ratio might be a more important risk factor than LDL-cholesterol itself in CAD patients, and should be investigated further. …”
Section: Article P 1392mentioning
confidence: 88%
“…3 They studied not only plaque volume but also the lipid pool area of atherosclerotic coronary arteries in chronic coronary artery disease (CCAD) and acute coronary syndrome (ACS) using integrated backscatter (IB) intravascular ultrasound (IVUS).…”
Section: Article P 1392mentioning
confidence: 99%
“…A recent large Danish cohort study investigating genotypes and nonfasting lipid levels for CAD risk demonstrated that a 1 mmol/L (39 mg/dL) increase in non-fasting RLP-C calculated as non-fasting total-cholesterol minus HDL-C minus LDL-C, was associated with a 2.8-fold increased causal risk for CAD, independent of reduced HDL-C level, whereas as 1 mmol/L increase in LDL-C was only associated with a 1.5-fold causal risk 49) . In addition, recent studies have shown that the LDL-C/ HDL-C ratio might be a positive predictor of progression and lipid-rich coronary plaque, which results in unstable coronary atherosclerotic lesion 15,50) . The Koba by Gensini score, elevated levels of BNP indicating advanced heart failure, the presence of diabetes and/or elevated HbA1c, decreases in eGFR, inflammation reflected by CRP levels, and advanced age were stronger predictors for cardiovascular events than lipid markers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TG to HDL ratio (TG/HDL) has been shown to indicate the presence of sdLDL particles and could serve as a good predictor of coronary heart disease (CHD) [15,16]. LDL to HDL ratio (LDL/HDL) was also found to predict CHD as do total cholesterol (TC) to HDL ratio (TC/HDL) and ApoB/ApoA-1 ratio [17,18]. However, effects of different types of glucose intolerance on non-HDL, TG/HDL and LDL/HDL are unclear.…”
Section: Introductionmentioning
confidence: 99%